Analiza oferty produktowej gospodarstw agroturystycznych w Polsce - Jacek Chotkowski; Małgorzata Czerwińska-Jaśkiewicz (Polityki Europejskie, Finanse i Marketing)
The main aim of this paper is to present the offer of agritourist farms in Poland. The authors demonstrate that their offers are highly diversified over regions. This stems from differences in the attractiveness of particular areas, social and economic factors, as well as policies laid down by local governments. Research has shown that farmers move towards enriching their services to tourists who want to stay in the countryside by offering cycle rental, as well as horse riding lessons or local sightseeing. Moreover, Polish hosts more and more often see the need to make use of regional attractions in terms of cultural life when designing the product for their visitors (e.g. regional dishes). The present paper was written on the basis of data contained in the catalogue titled “Poland-The Atlas of Agritourism. Welcome to the Countryside” published by the Polish Federation of Agritourism “Welcoming Farms” and also website www.agroturystyka.pl.